Quench Propagation in a TF Coil of the EU DEMO. (3rd October 2017) - Savoldi, L.; Bonifetto, R.; Brighenti, A.; Corato, V.; Muzzi, L.; Turtu', S.; Zanino, R.; Zappatore, A.
Abstract: The design of a suitable quench protection system is fundamental for the safe operation of superconducting magnets and in turn requires the accurate simulation of the quench transient. The quench propagation in a toroidal field (TF) coil for the future European fusion reactor (EU DEMO) is analyzed here considering the latest, layer-wound winding pack (WP) design proposed by ENEA. The thermal-hydraulic model of a TF coil implemented in the 4C code is updated by including the external cryogenic circuits of the WP and of the casing cooling channels and proposing a preliminary layout of the quench lines. Three different locations are considered for the quench initiation: maximum temperature margin in the WP, and minimum and maximum temperature margin on the same turn of the innermost layer. The evolution of the main electrical and thermal-hydraulic parameters is simulated, such as voltage along each layer, quench front propagation both along and across the layers, hot spot temperature, pressurization of the coil and coolant mass flow rate at the coil boundaries, so that the 4C code provides a reliable (in view of its validation) and detailed virtual monitor of what happens inside the coil during the quench transient. In all cases considered, the ENEA design is predicted to satisfy the present (i.e., ITER) design criteria concerning the maximum allowed hot spot temperature.